Libya's transition: Towards collapse - Wolfram Lacher (Stiftung Wissenschaft und Politik (SWP), 2014)
Escalating power struggles are driving Libya's transitional process towards collapse. Under the rallying cry of fighting terrorism, disparate political forces are seeking to suspend the transitional framework. They have no viable alternative to offer. External actors have insufficient influence to successfully mediate among the conflicting parties - but sufficient influence to complicate matters further. Western governments' ambiguous signals partly reflect a serious miscalculation: the expectation that the political forces supporting renegade general Khalifa Haftar can succeed in establishing a new transitional framework and stabilize the country. (SWP Comments)
Keywords: 320